2017
DOI: 10.1515/pjct-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

PANI/NaTaO3 composite photocatalyst for enhanced hydrogen generation under UV light irradiation

Abstract: A PANI/NaTaO 3 composite was successfully synthesized by an oxidative polymerization of aniline monomer in hydrochloric acid solution containing sodium tantalate. NaTaO 3 at a monoclinic structure was produced via hydrothermal method. The photocatalytic activities of the unmodifi ed NaTaO 3 and PANI/NaTaO 3 were evaluated for hydrogen generation from an aqueous HCOOH solution and under UV light irradiation. The results showed that the evolution rate of H 2 increased signifi cantly when NaTaO 3 was modifi ed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A composite of NaTaO 3 with PANI produces a two-times higher amount of hydrogen for the two hours of light irradiation than that of pristine NaTaO 3 [66]. The NaTaO 3 and PANI interfaces exhibit a low rate of charge recombination, which results in higher photocatalytic activity.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…A composite of NaTaO 3 with PANI produces a two-times higher amount of hydrogen for the two hours of light irradiation than that of pristine NaTaO 3 [66]. The NaTaO 3 and PANI interfaces exhibit a low rate of charge recombination, which results in higher photocatalytic activity.…”
Section: Photocatalytic Hydrogen Productionmentioning
confidence: 99%
“…Moreover, based on prior study done by Kato and Kudo in 1998, it was revealed that alkali tantalate is one of the most promising photocatalysts for the photo-decomposition of water under UV light irradiation [ 51 ]. Zielińska et al reported the loading of PANI on NaTaO 3 via oxidative polymerization in acidic solution containing sodium tantalate [ 52 ]. After 120 min of UV light illumination, the hydrogen production of PANI/NaTaO 3 reached about 2 times higher than that of pure NaTaO 3 .…”
Section: Polyaniline Based Photocatalystsmentioning
confidence: 99%
“…That study showed that polyaniline is an efficient conducting material for modifying CdS nanomaterials, for it enables better light penetration than does a polypyrrole shell. Zielińska et al [68] reported that the hydrogen production of PANI/NaTaO 3 photocatalyst under UV light irradiation was about twice that of pristine NaTaO 3 photocatalyst. PANI/NaTaO 3 exhibits a lower PL spectrum than that of NaTaO 3 , indicating a slower recombination of photoexcited charge carriers.…”
Section: Cadmium Sulfidementioning
confidence: 99%